Предмет: Алгебра,
автор: evteevtima
Упростите выражение 7(4x+y)-3(2x-y). В выражение2x-3y+1 подставте x=5ab,y=2ab-1 и выполнить преобразования
Ответы
Автор ответа:
0
7(4x+y)-3(2x-y)=28х+7у-6х+3у=22х+10у
2x-3y+1=2*5ab-3(2ab-1)+1=10ab-6ab+3+1=4ab+4
2x-3y+1=2*5ab-3(2ab-1)+1=10ab-6ab+3+1=4ab+4
Похожие вопросы
Предмет: Алгебра,
автор: amirrrrrch
Предмет: Физика,
автор: abobys2332
Предмет: Қазақ тiлi,
автор: ablaihansapiolda
Предмет: Математика,
автор: lili231623
Предмет: Математика,
автор: irinabatkovna